Comparative Evaluation of Dexmedetomidine and Bupivacaine Combination versus Bupivacaine Alone On the Analgesic Effect of Ilioinguinal Nerve Block in Pediatric Patients Undergoing Inguinal Herniorrhaphy - Sedighe Shahhosseini; Alireza Mahdavi (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: Elective inguinal herniorrhaphy is one of the most prevalent surgical procedures in pediatric age group. |Postoperative pain is prevalent in children undergoing inguinal hernia repair. This study was aimed to compare the analgesic effect of dexmedetomidine with bupivacaine combination versus bupivacaine alone for ilioinguinal nerve block in children undergoing inguinal herniorrhaphy.Materials and Methods: In this prospective randomized study, we studied 60 ASA class I and II patients with the age between 6 months to 6 years scheduled for unilateral inguinal herniorrhaphy. With the help of a computer-generated list, our patients were assigned randomly to two groups of 30 patients. Group A, received 5cc bupivacaine 0.25%, and group B received 5cc bupivacaine 0.25% with dexmedetomidine 0.3 μg/ kg. Statistical analysis was performed using SPSS. The t-student and Mann-Whitney tests were used to compare the variables between groups. The values were considered significant if P < 0.05.Results: There was no significant difference in blood pressure (systolic or diastolic) and heart rate between the two groups (P=0.624, P=0.784 and P=0.167, respectively).  Analgesia duration was significantly longer in bupivacaine with dexmedetomidine group in comparison to bupivacaine alone group (P=0.008). However, there were no significant difference in frequency of analgesic consumption (P = 0.175) and total dose of analgesic consumption (P = 0.634) in the first 24 h between the two groups. One patient in group B developed bradycardia.Conclusion: The use of dexmedetomidine, as an adjuvant to bupivacaine prolongs the length and the analgesic efficacy of the ilioinguinal nerve block after inguinal herniorrhaphy in pediatric age group.